Unequal synthesis and differential degradation of alpha and beta spectrin during murine erythroid differentiation (The Rockefeller University Press, 1988)
Murine erythroleukemia (MEL) cells represent a valuable system to study the biogenesis of the cytoskeleton during erythroid differentiation. When attached to fibronectin-coated dishes MEL cells induce, upon addition of DMSO, a 7-d differentiation process during which they enucleate and reach the reticulocyte stage (Patel, V. P., and H. F. Lodish. 1987. J. Cell Biol. 105:3105-3118); they accumulate band 3, spectrin, and ankyrin in amounts equivalent to those found in mature red blood cells. To follow the biosynthesis of spectrin during differentiation, membranes and cytoskeletal proteins of cells metabolically labeled with [35S]methionine were solubilized by SDS and alpha and beta spectrins were recovered by specific immunoadsorption. In both uninduced and 3-d induced cells, the relative synthesis of alpha/beta spectrin is approximately 1:3. In uninduced MEL cells newly synthesized alpha and beta spectrins are degraded with a similar half- life of approximately 10 h. In contrast, in 3-d differentiated MEL cells newly made beta spectrin is much more unstable than alpha spectrin; the half-lives of alpha and beta spectrin chains are approximately 22 and 8 h, respectively. Thus, accumulation of equal amounts of alpha and beta spectrin is caused by unequal synthesis and unequal degradation. As judged by Northern blot analyses, the level of actin mRNA is relatively constant throughout the 7-d differentiation period. alpha and beta spectrin mRNAs are barely detectable in uninduced cells, increase during the first 4 d of induction, and remain constant thereafter. In contrast, band 3 mRNA is first detectable on day 4 of differentiation. Thus, most of the spectrin that accumulates in enucleating reticulocytes is synthesized during the last few days of erythropoiesis, concomitant with the onset of band 3 synthesis. To determine whether this was occurring in normal mouse erythropoiesis, we analyzed the rate of appearance of labeled membrane proteins in mature erythrocytes after a single injection of [35S]methionine. Our results show that most of the spectrin and band 3 in mature erythrocytes is synthesized during the last days of bone marrow erythropoiesis, and that, in the marrow, band 3 and protein 4.1 are synthesized at a somewhat later stage of development than are alpha and beta spectrin, ankyrin, and actin.